First evidence of a “Barrovian”-type metamorphic regime in the Ross orogen of the Byrd Glacier area, central Transantarctic Mountains - TALARICO, F. M.; STUMP, E.; GOOTEE, B. F.; FOLAND, K. A.; PALMERI, R.; VAN SCHMUS, W. R.; BRAND, P. K.; RICCI, C. A. (Antarctic Science, 2007)
The Selborne Group comprises two metamorphic rock units, the muscovitedolomite bearing Madison Marble and the biotite-muscovitequartz-calcite Contortion Schist, which contains thick lenses of variably deformed metabasalts and metaconglomerates. Petrological and structural data indicate a polyphase metamorphic evolution including: i) an early stage of upper greenschist regional metamorphism (P = 0.15–0.3 GPa; T = 380–450°C), ii) prograde metamorphism during D1 up to amphibolite facies peak conditions (P = 0.58–0.8 GPa, T = 560–645°C), iii) syn-D2 unloading-cooling retrograde metamorphism, iv) a post-D2 contact metamorphic overprint at variable T between 450 and 550°C and 0.2 GPa connected to the emplacement of granitic plutons and felsic dyke swarms. Geochronological data constrain the polyphase syn-D1/D2 evolution between 510 and 492 Ma. A similar metamorphic path, including a medium P stage but at lower T conditions, is documented in greenschist facies metabasalts within the Byrd Group in the Mount Dick area. The metamorphic pattern and close lithostratigraphic matching between Selborne Group and Byrd Group sharply contrast with the high-grade Horney Formation that is exposed north of the Byrd Glacier and corroborate the hypothesis that the Byrd Glacier discontinuity marks a first-order crustal tectonic boundary crossing the Ross orogen.